Volatility component of derivative market: evidence from FBMKLCI based on CGARCH - Haron, Razali; Mansurat Ayojimi, Salami (Journal of Global Business and Social Entrepreneurship (GBSE), 2016)

(untitled)
This study examines the volatility component of Malaysian stock index. Despite extensive studies on stock index volatility, there are relatively few studies examining the volatility component of stock index in Malaysia. Using data from January 1, 2009 to December 31, 2013, this study aims to examine the volatility component of Malaysian stock index post financial crisis period, specifically on the mean-reversion, short-run (transitory) volatility, long-run (permanent) and speed of adjustment based on the generalized autoregressive conditional heteroskedasticity (GARCH). The finding reveals that both the KLCI and KLCI-Futures have persistence permanent volatility component, but transitory volatility components, on the other hand varies between the two markets. This study later confirms a faster mean-reversion in the KLCI-Futures comparative to KLCI. Nevertheless, the KLCI mean return remains positive during post crisis periods comparative to the futures market.